Activity of the Funai Fault and Radiocarbon Age Offsets of Shell and Plant Pairs from the Latest Pleistocene to Holocene Sediments Beneath the Oita Plain, Western Japan. Issue 6 (16th November 2017) - Nakanishi, Toshimichi; Takemura, Keiji; Matsuyama, Hisanori; Shimoyama, Shoichi; Hong, Wan; Okuno, Mitsuru
Abstract: Beppu Bay is located on east-central Kyushu, southwest Japan, and is characterized by hydrothermal activity, tectonic deformation, and recent volcanism under the influence of convergence of the Philippine Sea plate. This area, occupying the western portion of an arc-bisecting dextral fault system, is a tectonic depression that has existed since ca. 5 Ma. Sedimentary facies, mollusk assemblages, and radiocarbon ( 14 C) ages of 25 terrestrial plant fragments and 16 marine carbonate shells from a 70-m drill core were determined to estimate the activity of the Funai Fault, which consists of normal faults along the southern margin of the tectonic basin. Based on the analysis, six sedimentary facies, namely braided river channel, estuary, prodelta, delta front, delta plain, and artificial soil, were identified. The vertical slip rate was calculated as 2.6–2.7 mm/yr based on displacements of the braided river channel sediments of the last glacial period and the base of Kikai-Akayoya tephra in the Holocene highstand sediments of this area. Reservoir ages during 6180–10, 410 cal BP were determined from marine shell and terrestrial plant pairs from the sediments of the estuary, prodelta and delta front facies, and were correlated with values from a northern coast of Kyushu and the Korean Peninsula.